THE CLINICOPATHOLOGICAL PATTERN OF TESTICULAR TUMORS A 3-YEARS EXPERIENCE AT A TERTIARY CARE UROLOGY CENTER - Murtaza, Badar; Zafar, Muhammad Rafiq; Mirza, Zahoor Iqbal; Akmal, Muhammad; Ahmad, Hussain; Sajid, Muhammad Tanveer; Din, Hafeez Ud (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the clinical presentation of testicular tumors and their histological pattern present in our setup. Study Design: Case series. Place and Duration of Study: Armed Forces Institute of Urology (AFIU) Rawalpindi, from Jul 2016 to Jun 2019. Methodology: The documents of all the cases of testicular tumors presenting in the last 3 years were retrieved and their relevant clinical detail: age, clinical presentation, side of involvement, operative procedure conducted and the histopathology report were documented. Results: Thirty two patients of testicular tumors were documented over a period of three years, making 10.66 cases reporting per year. The mean age was 30.10 ± 15.42 years, with the youngest 3 months old infant and the eldest being 58 years of age. The tumors were commonest on the right (59.3%) with 81.2% presentation as swelling of testis. Radical orchiectomy was performed in 90.6% of the cases and retro peritoneal lymph node dissection (RPLND) in 6.2%. Germ cell tumors were found in 71.8% cases with mixed germ cell tumorbeing the commonest histopathology seen in 31.2% of the cases followed by the seminoma (25%) and non-Hodgkin lymphoma (12.5%). Conclusion: Testicular tumors were relatively uncommon in our part of the world with a limited number of cases presenting to a tertiary care urology center. The presentation was variable but a rising trend in non-Hodgkin lymphoma results in a decrease in the overall number of germ cell tumors.